Cardiac Function in 7-8-Year-Old Offspring of Women with Type 1 Diabetes - Rijpert, Maarten (Hindawi Publishing Corporation, 2011)
Offspring of type 1 diabetic mothers (ODMs) are at risk of short-term and long-term complications, such as neonatal macrosomia (birth weight >90th percentile), hypertrophic cardiomyopathy, and cardiovascular morbidity in later life. However, no studies have been performed regarding cardiac outcome. In this study, we investigated cardiac dimensions and function in 30 ODMs at 7-8 years of age in relation to neonatal macrosomia and maternal glycemic control during pregnancy and compared these with those in a control group of 30 children of nondiabetic women. We found that cardiac dimensions and systolic and diastolic function parameters in ODMs were comparable with those in controls. Neonatal macrosomia and poorer maternal glycemic control during pregnancy were not related to worse cardiac outcome in ODM. We conclude that cardiac function at 7-8 years of age in offspring of women with type 1 diabetes is reassuring and comparable with that in controls.